British politics in the global age : can social democracy survive? / Joel Krieger. - Krieger, Joel, 1951- (Polity, 1999)
Krieger's study of New Labour's model of government and the political challenges it faces provides an analysis of the interaction of global processes and domestic politics as considered from a British standpoint.